Influence of Digital Literacy on the Critical Thinking Ability of Mathematics Education Students in Evaluating Digital Information - Syamsinar Syamsinar; Fadhilah Nur Sa’diyyah; Mulyana Mulyana (Kognitif: Jurnal Riset HOTS Pendidikan Matematika, 2026)
Students’ critical thinking skills in assessing digital information have not yet developed optimally. This study aims to analyze the relationship between digital literacy and the critical thinking ability of mathematics education students in evaluating digital information. The research employed a quantitative approach with a correlational design. The participants consisted of 120 students from the Department of Mathematics Education at Universitas Negeri Makassar, selected through purposive sampling. The research instruments included a digital literacy questionnaire measuring aspects of access, evaluation, verification, and utilization of digital information, as well as a critical thinking test assessing information analysis, source credibility evaluation, information verification, and conclusion drawing. The validity test results indicated that all instrument items had validity coefficients above 0.30 and were therefore considered valid, while the reliability test results showed Cronbach’s Alpha values of 0.87 for the digital literacy questionnaire and 0.82 for the critical thinking test, indicating that both instruments were reliable. Data were analyzed using descriptive statistics and simple linear regression analysis. The findings revealed that students’ digital literacy was categorized as high, whereas their critical thinking ability was categorized as moderate based on the predetermined score intervals. Regression analysis demonstrated that digital literacy had a positive and significant predictive relationship with students’ critical thinking ability (β = 0.48; p < 0.001), contributing R² = 0.32. This study recommends integrating digital literacy into mathematics learning through activities involving source evaluation, information analysis, and evidence-based argumentation to support the development of students’ critical thinking skills.